Examining the Industrial Impact of Fintech Lending in the Post-Next Normal Era - Ramdhan, Nur 'Asyiqin; Bujang, Imbarine; Muhamat, Amirul Afif; Lisdiono, Purwatiningsih (UI Scholars Hub, 2025)
The financial sector has undergone a substantial paradigm shift as a consequence of the COVID-19 pandemic prompting industries actively innovate their financing method. Utilizing ARDL, our analysis reveals intriguing insights into the interaction of financing determinants interruptions caused by the epidemic, and the P2P lending success. The long-term effects of economic conditions alluding to the significant influence of investment size across various industrial sectors. The industrial differences suggest interesting connections between the size of investments, and loan tenure to the P2P lending in different industries. The wholesale and retail trade sector demonstrates intricate reactions to changes in investment size, while manufacturing sector impacted by BLR. Conversely, the susceptibility of the agriculture sector to exogenous shocks presents a captivating narrative for the investigation. Our study provides significant contributions to the complex domain of P2P lending in the context of global disruptions.